VIRTUAL SCREENING AND MOLECULAR DOCKING OF NDM1 INHIBITOR FOR TREATMENT OF KLEBSIELLA PNEUMONIA INFECTION: Life Sciences-Bioinformatics - C.THIYAGARAJAN; P.THIRUMALAIVASAN (International Journal of Life Science and Pharma Research, 2022)
The outbreak of antimicrobial resistance has become one of the most serious public health problems across in the world. The search for promising antimicrobial inhibitors is still under limelight as bacteria are continuously developing resistance to antimicrobial compounds. The Metallo-β-lactamases (MβLs) is one the New Delhi metallo‐beta‐lactamase 1 (NDM-1) are principle contributors of the emergence of resistance to their ability to hydrolyze almost all known β-lactam antibiotics including penicillins, cephalosporins, and carbapenems. In this study, we used the computer assisted methodology such as virtual screening and molecular docking studies to apply and identify six potent inhibitors against NDM1.